The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1073/pnas.2009156118
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence that KNDy neurons maintain gonadotropin pulses and folliculogenesis as the GnRH pulse generator

Abstract: The gonadotropin-releasing hormone (GnRH) pulse is fundamental for mammalian reproduction: GnRH pulse regimens are needed as therapies for infertile women as continuous GnRH treatment paradoxically inhibits gonadotropin release. Circumstantial evidence suggests that the hypothalamic arcuate KNDy neurons expressing kisspeptin (encoded by Kiss1), neurokinin B (encoded by Tac3), and dynorphin A serve as a GnRH pulse generator; however, no direct evidence is currently available. Here, we show that rescuing >20%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
72
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 63 publications
(77 reference statements)
3
72
1
Order By: Relevance
“…This is because plasma LH/FSH levels were undetectable in global Kiss1 knockout rats ( 58 ), in which Tac3 and Pdyn gene were abundantly expressed in the ARC as shown in wild-type female rats. Further, Kiss1 rescue into the ARC Tac3 -expressing cells but not out of the Tac3 -expressing cells rescued LH pulses in the global Kiss1 knockout female rats ( 123 ). These findings indicate that ARC neurokinin B/dynorphin A neurons without Kiss1 could not drive GnRH/LH pulse generation.…”
Section: Direct Evidence That Kndy Neurons As the Gnrh Pulse Generatormentioning
confidence: 93%
See 2 more Smart Citations
“…This is because plasma LH/FSH levels were undetectable in global Kiss1 knockout rats ( 58 ), in which Tac3 and Pdyn gene were abundantly expressed in the ARC as shown in wild-type female rats. Further, Kiss1 rescue into the ARC Tac3 -expressing cells but not out of the Tac3 -expressing cells rescued LH pulses in the global Kiss1 knockout female rats ( 123 ). These findings indicate that ARC neurokinin B/dynorphin A neurons without Kiss1 could not drive GnRH/LH pulse generation.…”
Section: Direct Evidence That Kndy Neurons As the Gnrh Pulse Generatormentioning
confidence: 93%
“…To prove that KNDy neurons serve as the GnRH pulse generator, we rescued KNDy neurons by infecting viral vectors expressing Kiss1 mRNA targeted into the ARC Tac3 -expressing neurons in global Kiss1 knockout female rats ( 123 ). Pulsatile LH release was recovered in KNDy-rescued rats in which 20-50% ARC Tac3 -expressing neurons exhibited Kiss1 expression.…”
Section: Direct Evidence That Kndy Neurons As the Gnrh Pulse Generatormentioning
confidence: 99%
See 1 more Smart Citation
“…Stim1 kko mice exhibited more estrous-type vaginal cytology, which may be indicative of higher levels of circulating estrogens due to increased synchronous firing of kisspeptin neurons and excitatory drive to GnRH neurons (Qiu et al, 2016;Clarkson et al, 2017). It is important to note that synchronous firing of "pulse generator" Kiss1 ARH neurons is a failsafe system for maintaining gonadotropin pulses and folliculogenesis in female rodents (Nagae et al, 2021).…”
mentioning
confidence: 99%
“…Loss of function studies of kisspeptin or GPR54 by genetic mutation or conventional knockout showed hypogonadotropic hypogonadism with low to undetectable luteinizing hormone (LH) levels, which clearly demonstrates that kisspeptin-GPR54 signaling is a fundamental factor for stimulating GnRH/LH secretion in rodents and humans [16][17][18]. Kisspeptin neurons located in the hypothalamic arcuate nucleus (ARC) coexpress neurokinin B (NKB) and dynorphin A (Dyn) in rats [19][20][21], mice [22], guinea pigs [23], sheep [24], and goats [25], and are therefore referred to as KNDy neurons [9], and suggested to be the GnRH/LH pulse generator [25][26][27][28][29][30][31].…”
mentioning
confidence: 99%